PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Dini Fitrianti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to analyze the influence of tax planning and deferred tax burden on earnings management. The population in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2018-2022. This data collection technique is secondary data with data collection methods, namely literature study and documentation. The sample obtained was 34 companies using the E-Views series 12 statistical tool. The analysis technique used was panel data regression. The results of this study indicate that partial tax planning has no effect on Earnings Management. Deferred Tax Expenses partially influence Earnings Management. Tax Planning and Deferred Tax Expenses simultaneously have a significant influence on Earnings Management. Keywords: earnings management, tax planning, deferred tax expenses